(untitled) (Journal of the College of Basic Education, 2022)
From the above clarification, we conclude that the position of secularism in Islamic thought varied according to the intellectual orientations and Islamic, liberal and nationalist currents, and this contrast differed in its intensity according to the reference of the currents, and we can say:- Secularism is a foreign concept to the Arab state and Islam, as it means separation between religion and state, despite the diversity of its definition and verbal reasoning. As it came in an environment completely different from the Arab-Islamic environment, the clash between the church and the ruler in Europe and the effects it generated and spread of fears were reflected in the crystallization of ideas rejecting the interference of religious authority with political authority and curtailing the role of the Pope and the Church with the increase in enlightenment movements